Education of the next generation of managers in context of green economy - Chovancova, Jana; Harausová, Helena (Journal of Economic Development, Environment and People, 2013)
This paper deals with the issue of education for sustainable development of the generation of future managers in the context of the green economy. The paper analyses the need for environmental education of graduates in theoretical way who are expected to act as executives and in positions which are defined as Green Enhanced Skills Occupations or shortly Green Jobs and who should be able to apply the tools of environmental protection in a business sector, municipalities or third sector. The essential part of the article presents the partial results of the research, which was focused on finding whether students of economic universities are aware of issue of sustainable development and environmental policy tools, which can help the implementation of green economy in the practice and whether this issue is taught at universities. At the end of the article authors point out the important role of universities in preparing the future managers to work in the green economy.